GE_GERICHTE C/20654/2012 vom 24. Juni 2013 - GE Cour de justice (2013)
COMMUNICATION; NOTIFICATION IRRÉGULIÈRE; INTERPRÉTATION(SENS GÉNÉRAL); CONDITIONS GÉNÉRALES DU CONTRAT; DOMICILE ÉLU | CPC.133.a; CO.18; Cst.29; CC.2